Role of denosumab in the management of skeletal complications in patients with bone metastases from solid tumors - Stopeck AT (Dove Medical Press, 2012)
Ursa Brown-Glaberman, Alison T StopeckUniversity of Arizona Cancer Center, Tucson, AZ, USAAbstract: Skeletal-related events (SREs) including pain, fractures, and hypercalcemia are a major source of morbidity for cancer patients with bone metastases. The receptor activator of NF-κB ligand (RANKL) is a key mediator of osteoclast formation and activity in normal bone physiology as well as cancer-induced bone resorption. The first commercially available drug that specifically targets and inhibits the RANKL pathway is denosumab, a fully human monoclonal antibody that binds and neutralizes RANKL, thereby inhibiting osteoclast function. In this review, we summarize the major studies leading to the US Food and Drug Administration-approval of denosumab for the prevention of SREs in patients with bone metastases from solid tumors. Further, we discuss the role of denosumab in the prevention and treatment of SREs and bone loss in cancer patients. As a monoclonal antibody, denosumab has several advantages over bisphosphonates, including improved efficacy, better tolerability, and the convenience of administration by subcutaneous injection. In addition, as denosumab has no known renal toxicity, it may be the preferred choice over bisphosphonates in patients with baseline renal insufficiency or receiving nephrotoxic therapies. However, other toxicities, including osteonecrosis of the jaw and hypocalcemia, appear to be class effects of agents that potently inhibit osteoclast activity and are associated with both denosumab and bisphosphonate use. The data presented highlight the differences associated with intravenous bisphosphonate and denosumab use as well as confirm the essential role bone-modifying agents play in maintaining the quality of life for patients with bone metastases.Keywords: denosumab, bone metastases, solid tumor, breast cancer, prostate cancer, skeletal related events, skeletal complications